Biodegradation of hydrocarbons in polluted soils using β-cyclodextrin as a coadiuvant - S. Steffan; L. Bardi; M. Marzona (ՀՀ ԳԱԱ հրատ.)
The biodegradation of pollutants depends on their biovailability for soil microorganisms.
Keywords: Biology; Biochemistry